Freedom of Conscience as a Subject of Contemporary Controversies - Machinek, Marian (Collectanea Theologica, 2021)
One of the important reasons why the issue of freedom of conscience is one of the most controversial problems of modern times is the ongoing dispute over its definition. In the context of the contemporary emphasis on the moral autonomy of the person, the recent definitions of conscience as the “voice of God” sound at least ambiguous. It is therefore important to point out the various dimensions of conscience. The first and basic one is the individual dimension: conscience is defined as moral self-consciousness in its deepest, personal dimension. It can therefore, following E. Fromm, be described as the “guardian of moral integrity.” However, in addition to this, conscience also points out to “what is common” (J. Ratzinger), to the fundamental values that make social life possible. It is therefore also a carrier of moral truth. Finally, conscience touches upon the relationship with God and this is where its important religious dimension is expressed. It is only when each of these three dimensions of conscience is taken into account that the question of its freedom can be adequately considered. It concerns, above all, the relationship of an individual conscience to an external authority, both in social and ecclesiastical context.